(untitled) (Journal of Kidney Cancer, 2020)
Aim: “To evaluate oncological and surgical outcomes of different levels of tumor thrombus and tumor characteristics secondary to renal cell carcinoma (RCC)”. Materials and Methods: Retrospective review from 2013 to 2020 of 34 patients who underwent radical nephrectomy with thrombectomy for RCC with tumor thrombus extending into the inferior vena cava (IVC) and right atrium (RA) at our center. Level I and most level II tumors were removed using straight forward occluding maneuvers with control of the contralateral renal vein. None of the patients had level III tumor extensions in our study group. For level IV thrombus, a beating heart surgery using a simplified cardiopulmonary bypass (CPB) technique was used for retrieval of thrombus from the right atrium. Results: “Of the 34 patients with thrombus”, 19 patients had level I, 12 patients had level II, none had level III, and three patients had level IV thrombus. Two patients required simplified CPB. Another patient with level IV thrombus CPB, was not attempted in view of refractory hypotension intraoperatively. Pathological evaluation showed clear-cell carcinoma in 67.64%, papillary carcinoma in 17.64%, chromophobe in 5.8%, and squamous cell carcinoma in 8.8% of cases. Left side thrombectomy was difficult surgically, whereas right side thrombectomy did not have any survival advantage. Mean blood loss during the procedure was 325 mL, ranging from 200 to 1000 mL, and mean operative time was 185 min, ranging from 215 to 345 min. The immediate postoperative mortality was 2.9%. Level I thrombus had better survival compared to level II thrombus. Conclusion: Radical nephrectomy with tumor thrombectomy remains the mainstay of treatment in RCC with inferior venacaval extension. The surgical approach and outcome depends on primary tumor size, location, level of thrombus, local invasion of IVC, any hepato-renal dysfunction or any associated comorbidities. The higher the level of thrombus, the greater is the need for prior optimization and the adoption of a multidisciplinary approach for a successful surgical outcome.